A new visual approach with the concentration calibration method for the hydrogen leakage and distribution research. (15th August 2023) - Li, Jianwei; Tian, Zhonghao; Yang, Qingqing; Feng, Lili; Su, Hongyan; Lan, Hao
Highlights: The relationship between hydrogen concentration and gray value is decoupled. A quantitative visual measurement method for hydrogen concentration is proposed. Axial/radial attenuation of jet concentration is calculated from the visual image. The effect of initial hydrogen content on concentration distribution is considered. Abstract: Hydrogen security is an intrinsic requirement for the increasing development of hydrogen energy. The evolutional regularity of hydrogen leakage including hydrogen concentration and its distribution plays a key role in hydrogen leakage prevention, hence essential for safety research. It is difficult to measure hydrogen concentration distribution covering the whole area as a measurement plane due to the discreteness or invasiveness of the conventional sensing method. To solve the problem, this paper proposed a new method for quantitative analysis of hydrogen leakage distribution with a visual imaging experiment. Firstly, a series of imaging experiments under different leakage concentrations were performed based on the schlieren technique. A new calibration method is developed to deal with the mapping relationship between the jet leakage concentration and the gray value of the schlieren image. Therefore, the different gray values of the schlieren image are labeled as different hydrogen concentrations. Then, by extracting the quantitative concentration information in the axial and radial direction of the schlieren image, the concentration attenuation formulas in these two directions can be obtained. The proposed visual approach together with the gray calibration method are verified by comparative experiments, and the attenuation formula accurately represents the jet concentration distribution with an average error of less than 10%.